2014
DOI: 10.1108/sej-05-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and the target population

Abstract: Purpose – The purpose of this article is to shed light on opportunities for social capital during the conceptualization and initial implementation of innovative social enterprises dedicated to violence prevention and youth empowerment in Brazil. Design/methodology/approach – Based on a two-tiered interview process over a nine-month period with 27 social entrepreneurs in Rio de Janeiro, Brazil, attention is given to with whom, where and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Additionally, three further control variables were found to have a positive impact on SE intentions. Specifically, prior experience with social problems (Comunian and Gielen, 1995; Scheiber, 2014) and female gender (Coskun et al , 2019; Ernst, 2011; Hechavarria et al , 2012) had a positive impact on SE intentions. Looking at the difference between women and men more closely using a t -test and histograms, men’s social entrepreneurial intentions are more positively distributed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, three further control variables were found to have a positive impact on SE intentions. Specifically, prior experience with social problems (Comunian and Gielen, 1995; Scheiber, 2014) and female gender (Coskun et al , 2019; Ernst, 2011; Hechavarria et al , 2012) had a positive impact on SE intentions. Looking at the difference between women and men more closely using a t -test and histograms, men’s social entrepreneurial intentions are more positively distributed.…”
Section: Resultsmentioning
confidence: 99%
“…In our decision to include prior experience with social problems, we followed Comunian and Gielen (1995), who found that an individual’s social experience influences their moral judgment. Similarly, Scheiber (2014) reported that social entrepreneurs in Rio de Janeiro have one or more direct socioeconomic experiences, such as addressing a disparity in society, volunteering or taking part in religious, social or political activism.…”
Section: Methodsmentioning
confidence: 99%
“…There have been few studies on how SEs brought about an increase in participation of individuals by taking SE initiatives based on trust. (Scheiber, 2014). However, even such studies have focused little on trust per se in SE literature (Tack et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Mair and Marti (2006) state that social capital helps social entrepreneurs relieve social problems and enter the public sphere. Scheiber (2014) finds that social capital allows social entrepreneurs to develop a better understanding of complex social problems, which results in more effective social entrepreneurship initiatives.…”
mentioning
confidence: 99%
“…Trust facilitates cooperative behavior, decreases detrimental conflict, reduces transaction costs, promotes network relations, enables swift formulation of ad hoc work groups, and promotes effective responses to crises (Rousseau, Sitkin, Burt, & Camerer, 1998); all of which are critical in social entrepreneurship efforts. Scheiber's (2014) analysis of 27 social entrepreneurs in Rio de Janeiro found trust to be instrumental in increasing participation in social entrepreneurship initiatives, gaining access to additional members of the target population, and achieving greater levels of effectiveness and social impact. Nevertheless, very little existing social entrepreneurship literature explicitly focuses on trust.…”
mentioning
confidence: 99%